PENDAMPINGAN PEMBUATAN PUPUK BOKASHI BAGI PETERNAK SAPI POTONG DI DESA HUTABOHU KECAMATAN LIMBOTO BARAT KABUPATEN GORONTALO - Ilham, Fahrul; Djunu, Sri Suryaningsih; Syahruddin; Pateda, Sri Yenny; Mas’ud, Muhammad Sayuti (Jurnal Abdi Insani, 2024)
Hutabohu Village has the potential to support the development of beef cattle. One of the problems with beef cattle farming in Hutabohu Village is the accumulation of manure around the pen area. The solution to this problem is bokashi technology to reduce the impact of air pollution. The benefits of this service activity include increasing awareness and desire of village residents to use livestock manure to make bokashi, reducing the cost of purchasing chemical fertilizers, maximizing the integration of agriculture and livestock. The aim of this Community Service (PPM) activity is to increase the knowledge and skills of residents in Hutabohu Village in processing and utilizing beef cattle dung waste into organic fertilizer.  The location of this service is the Iloheluma livestock group in Hutabohu Village, West Limboto District, Gorontalo Regency. The duration of the activity is 2 months (April-May 2024). Providing theory by means of counseling and continuing with the practice of making bokashi with students participating in MBKM-KKN from UNG. The results of the implementation show that the stages of making bokashi in Hutabohu Village include preparing the ingredients (cow dung, EM-4, molasses, water, rice husk ash, rice bran), mixing all the ingredients, and incubation for 2 weeks. Indicators of the success of bokashi are that the color becomes blacker and resembles soil, does not clump when opened from the hand, does not smell like dirt, and there is no mold in the middle. The application of bokashi for plants is spread on the surface of agricultural land, given directly to the planting hole, mixed with soil in polyback. Participants' enthusiasm during the activity was quite high, reflected in their presence and active discussions until the end of the training. Conclusion: Making organic bokashi fertilizer can be an option for Hutabohu Village residents to be more efficient and effective in raising beef cattle.